Between ritual and information: Three phases of Norwegian news audiences' sense-making of the election of Donald Trump. (November 2021) - Moe, Hallvard; Ytre-Arne, Brita; Nærland, Torgeir Uberg
This article investigates sense-making processes of news audiences when faced with destabilizing global events. The destabilizing event is Trump's 2016 election win, which we study from the perspective of audiences far removed: in the Nordic region. Asking how we can understand shifts in the balance between the informational and ritual aspects of news over time, we study how journalism matters when ordinary practices are suddenly uprooted, and in the gradual return to everyday life. Based on the analysis of extensive qualitative material, we formulate three successive phases of Norwegian news audiences' reactions to the election: annoying circus far away, world-shattering shock and regained stability. We underline not only shared experiences but also nuances which we link to differences in media use routines, levels of interests in news as well as resources for the sense-making of politics. Our findings contribute to the scrutiny of news use in everyday life and at times of political upheaval, and add an audience perspective to research on Trump and the media.